PENGEMBANGAN MODUL PERMAINAN TRADISIONAL UNTUK MENUMBUHKAN SIKAP HORMAT ANAK USIA 6-8 TAHUN - Dian Tri Cahyani Whardhaya; Gregorius Ari Nugrahanta (Fakultas Ilmu Pendidikan Universitas Negeri Surabaya, 2022)
This traditional game is a culture that is almost extinct. This research aims to develop a traditional game module to cultivate respect for children aged 6-8 years. The research method used is research and development (R&D) type ADDIE. The result showed. 1) The traditional game module was developed based on the steps in the ADDIE method, namely Analyze, Design, Develop, Implement, and Evaluate. 2) The validation show score 3,80 on a scale 1 to 4 with the quality results of the traditional game modules very well and recommendation without any improvement. 3) The application of traditional game module affects the respect character of children. The significance test showed t = 5,534 and p < 0.05. The amount of influence is r = 0.93 or equivalent to 85.97% (large effect). It means that the application of traditional game modules affected changes in children’s respect by 85,97%. The traditional game module showed high effectiveness with a score of 79.16% as evidenced by the N-gain score.